Comparison of group motivational interviewing and multimedia education on elderly lifestyle - Mahmoud Movahedi; Feryal Khamseh; Abbas Ebadi; Zahra Hajiamini; Ali Navidian (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Many of the problems caused by aging can be delayed and the health of the elderly maintained by improving and applying a healthy lifestyle during old age. Therefore, the researcher has designed and implemented a study aimed "compare the impact of group motivational interviews with multimedia education on improving lifestyle in the elderly." METHODS: This study is triple blind before and after clinical trial was performed on three groups of thirty (n = 90) of the elderly with mean age 63.41 ± 6.88 who were members of the elderly centers of Tehran city neighborhoods with average to unfavorable lifestyle score. The first test group was subjected to group motivational interviewing during five sessions. The second test group was subjected to distant multimedia training. No training was given to the third group as the control group. After 3 months, the lifestyle questionnaire was completed in three groups. The results were analyzed by these techniques as statistical tests such as mean, standard deviation, relative frequency, and absolute frequency were used. The inferential statistical tests such as paired t-test and one-way ANOVA were used, respectively, to compare the pre- and post-mean scores and in each group and compare the mean scores of lifestyle dimensions in three groups. RESULTS: Both motivational interviewing and multimedia education have been effective in changing the lifestyle of the elderly, but according to the findings, motivational interviewing has a greater impact on elderly lifestyle. The total lifestyle score in four areas such as nutrition, self-care, mental health, and physical activity was significantly different in the three groups after the intervention (P < 0.001). CONCLUSIONS: Each educational program can somehow improve behavioral skills in individuals. Effective teaching methods should address the learning difficulties and inability to learn during the aging period. The results of this study can be a step toward the elaboration of strategies for education and promotion of healthy lifestyle in the elderly.